2016
DOI: 10.1590/s1980-5764-2016dn1004014
|View full text |Cite
|
Sign up to set email alerts
|

The perception of apathy by caregivers of patients with dementia in Parkinson's disease

Abstract: BackgroundApathy is one of the main neuropsychiatric symptoms in patients with Parkinson's disease (PD) and is associated with Parkinson's disease dementia (PDD).ObjectiveTo identify the characteristics of apathy in individuals with PDD according to caregiver perception.MethodsThirty-nine patients with PD according to MDS criteria for PDD were included. The following scales were used: the Hoehn and Yahr, the Unified Parkinson's Disease Rating Scale III, Scales for Outcomes in Parkinson's Disease-Cognition (SCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It can be characterized as diminished motivation or even lack of motivation and loss of initiative. Apathy is a longlasting state that is associated with increased mortality and a substantially greater burden for caregivers ( Harrison et al., 2016 ; Camargo et al., 2016 ; Nijsten et al., 2017 ; Terum et al., 2017 ); however, a Japanese study found apathy, anxiety, and depression not to seriously aggravate caregiver burnout. A higher level of burnout was related to agitation/aggression, irritability, aberrant motor behavior, and hallucinations ( Hiyoshi-Taniguchi et al., 2018 ).…”
Section: Review Of Current Knowledge On Bpsd Managementmentioning
confidence: 99%
“…It can be characterized as diminished motivation or even lack of motivation and loss of initiative. Apathy is a longlasting state that is associated with increased mortality and a substantially greater burden for caregivers ( Harrison et al., 2016 ; Camargo et al., 2016 ; Nijsten et al., 2017 ; Terum et al., 2017 ); however, a Japanese study found apathy, anxiety, and depression not to seriously aggravate caregiver burnout. A higher level of burnout was related to agitation/aggression, irritability, aberrant motor behavior, and hallucinations ( Hiyoshi-Taniguchi et al., 2018 ).…”
Section: Review Of Current Knowledge On Bpsd Managementmentioning
confidence: 99%
“…A variety of studies assessed differences between self versus caregiver rated versions of non-motor symptom screening tools. [47][48][49][50] It was reported that where a screening tool is administered to the caregiver, apathy scores are higher; this is thought to be due to caregivers increased awareness of the presence and severity of apathy in those they are caring for. [47][48][49][50] Two per cent of studies that did not employ any screening tools used clinical interviews to identify apathy.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Further observations regarding diagnostic processes include, understanding discrepancies between caregiver and self-rated apathy screening tools. [47][48][49][50] This may be due to the inherent nature of apathy, in that persons with PD and apathy have limited awareness of their behaviour, and therefore assess themselves as less apathetic (e-40, e-44). Cognitive decline that often presents with apathy may impair one's ability to accurately respond to selfrated tools (e-40, e-44).…”
Section: Diagnosismentioning
confidence: 99%